PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA MATERI PENCEMARAN LINGKUNGAN MTS NEGERI SUNGAI PINYUH - Nuria, Rika; Masriani, Hairida; Masriani, Masriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purposes of this study are to describe the scientific work skill of students before and after the guided inquiry learning model is applied to the material environmental pollution and to determine the different scientific work skills of students MTs Negeri Sungai Pinyuh academic year 2017/2018. This study uses a pre-experimental research design one group pretest-posttest. The sample in this study were students of class VII B by purposive sampling technique. The research technique of data collecting is a measurement technique using pretest-posttest, direct observation and interview. After data processing, the results show that the pretest scientific work skills of students that are in the category ofÂ  less skilled, and unskilled respectively by 12.12% and 87.88%, while the results show that the posttest scientific work skills of students that are in the category of highly skilled, skilled, and less skilled in a row amounted to 9.38%, 78.12%, and 12.5%. Wilcoxon test results showed there were differences of scientific work skills before and after taught with guided inquiry.Â Keyword: Scienific Work Skill, Guided Inquiry, Enviromental PollutionÂ